Virulence-inhibitory activity of the degradation product 3-hydroxybutyrate explains the protective effect of poly-β-hydroxybutyrate against the major aquaculture pathogen Vibrio campbellii - Defoirdt, Tom (Sci Rep, 2018)
The bacterial storage compound poly-β-hydroxybutyrate, a polymer of the short-chain fatty acid 3-hydroxybutyrate, has been reported to protect various aquatic animals from bacterial disease. In order to obtain a better mechanistic insight, we aimed to (1) investigate whether 3-hydroxybutyrate is released from poly-β-hydroxybutyrate within sterile brine shrimp larvae, (2) determine the impact of 3-hydroxybutyrate on the virulence of Vibrio campbellii to brine shrimp larvae and on its cell density in the shrimp, and (3) determine the impact of this compound on virulence factor production in the pathogen. We detected 3-hydroxybutyrate in poly-β-hydroxybutyrate-fed brine shrimp, resulting in 24 mM 3-hydroxybutyrate in the intestinal tract of shrimp reared in the presence of 1000 mg l(−1) poly-β-hydroxybutyrate. We further demonstrate that this concentration of 3-hydroxybutyrate does not affect the growth of V. campbellii, whereas it decreases the production of different virulence factors, including hemolysin, phospholipase and protease activities, and swimming motility. We hypothesize that by affecting all these virulence factors at once, 3-hydroxybutyrate (and thus also poly-β-hydroxybutyrate) can exert a significant impact on the virulence of V. campbellii. This hypothesis was confirmed in a challenge test showing that 3-hydroxybutyrate protected gnotobiotic brine shrimp from pathogenic V. campbellii, without affecting the number of host-associated vibrios.